2007
DOI: 10.1109/tasc.2007.899876
|View full text |Cite
|
Sign up to set email alerts
|

${\hbox{MgB}}_{2}$ for Application to RF Cavities for Accelerators

Abstract: Magnesium diboride (MgB 2 ) has a transition temperature (T c ) of 40 K, i.e., about 4 times as high as that of niobium (Nb). We have been evaluating MgB 2 as a candidate material for radio-frequency (RF) cavities for future particle accelerators. Studies in the last 3 years have shown that it could have about one order of magnitude less RF surface resistance (R s ) than Nb at 4 K. A power dependence test using a 6 GHz TE 011 mode cavity has shown little power dependence up to 12 mT (120 Oe), limited by availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This technique allows one to prepare large MgB 2 objects, as it has been demonstrated elsewhere [13]. In particular, a steel tube with an internal diameter of 4 mm has been filled by crystalline B powder of average sizes less than 38 lm (99.5% purity) and the powder has been pressed reaching a packing density of almost 1.4 g/cm 3 . At the ends of the container, two cylinders of Mg have been put in contact with the B powder and the whole system has been subjected to a thermal treatment at 850°C for 3 h. The resulting MgB 2 rod has been machined out of the reaction container to have a diameter of 3.8 mm and a length of 94.3 mm.…”
Section: Coaxial Cavity: Theoretical Aspects and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique allows one to prepare large MgB 2 objects, as it has been demonstrated elsewhere [13]. In particular, a steel tube with an internal diameter of 4 mm has been filled by crystalline B powder of average sizes less than 38 lm (99.5% purity) and the powder has been pressed reaching a packing density of almost 1.4 g/cm 3 . At the ends of the container, two cylinders of Mg have been put in contact with the B powder and the whole system has been subjected to a thermal treatment at 850°C for 3 h. The resulting MgB 2 rod has been machined out of the reaction container to have a diameter of 3.8 mm and a length of 94.3 mm.…”
Section: Coaxial Cavity: Theoretical Aspects and Designmentioning
confidence: 99%
“…Although MgB 2 SC has been indicated by several authors as suitable material for mw application [1][2][3], the frequency dependence of R s in this material has not been comprehensively investigated. Up to now, in the literature there are only few papers discussing results of frequency dependence of R s , obtained mainly in MgB 2 films [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, MgB 2 thin films have been produced and employed in the study of two-gap superconductivity in MgB 2 . Furthermore, the high-quality MgB 2 thin films are very suitable for engineering applications, such as superconducting electronic devices [37] and radio-frequency (RF) cavities [38,39]. For example, Nb-based RF cavity technology is now very close to theoretical limits [38] and high-quality single-crystalline MgB 2 thin films are considered to be the most plausible candidates [39] for meeting the still expanding requirements of accelerator research.…”
Section: Single-crystal Like Mgb 2 Thin Filmsmentioning
confidence: 99%
“…Since the discovery of MgB 2 superconductor with T c ≈ 39 K, several authors have indicated this material as promising for mw applications [5]- [7], looking particularly at the realization of mw cavities for particle accelerators. Still now, several groups investigate the properties of MgB 2 with the aim to demonstrate its suitability for mw applications, particularly in films [8]- [10].…”
Section: Introductionmentioning
confidence: 99%